A field study on social behaviour, feeding regime and health status in semi-captive and free-ranging Orang Utans (Pongo pygmaeus) undergoing rehabilitation programme - A. B., Salina; N. B., Salim; Abdullah, Rasedee; Senthilvel, K. S. S. N. (Universiti Putra Malaysia Press, 2004)
The study was conducted at the Orang Utan Rehabilitation Centre (OURC) in Sabah and the Wildlife Centre (WC) in Sarawak with a population of 43 and 10 orangutans respectively. The result showed that both semicaptive and free-ranging orangutans spent 30.7% of their daytime climbing, 28.4% swinging, 24.3% playing and 16.6% resting. The free-ranging orangutans showed extra social behaviours such as foraging, nest-building, socialising and aggression. Even though the diet of the orangutans was dependent on the food provided by the keepers, papaya seemed to be their favourite food. The health evaluation revealed the body temperature at 36.1-36.5∞C, pulse rate at 115-121 bpm and respiratory rate at 24-28 bpm were within normal range. The measurement of the body weight indicated the growth rate at 0.3 kg per week for juvenile orangutans and 0.004 kg per week for infant orangutans over a 4-week period. The haematological and serum biochemistry analyses gave normal values of the blood and serum parameters. Parasitological analyses using simple floatation technique detected three nematodes (Oesophagostomum sp., Trichuris trichuria, Strongyloides stercoralis) and one protozoon (Balantidium coli).